2014
DOI: 10.1097/shk.0000000000000113
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvate Is Superior to Reverse Visceral Hypoperfusion in Peritoneal Resuscitation From Hemorrhagic Shock in Rats

Abstract: Peritoneal resuscitation with hyperosmolar fluids attenuated visceral vasoconstriction and splanchnic hypoperfusion and improved the intestinal barrier protein and organ function following conventional fluid resuscitation from severe HS in rats. Pyruvate was superior to lactate in PDS as PR fluids, and 2.2% pyruvate was the optimal fluid in PR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 25 publications
1
14
1
Order By: Relevance
“…Even though we did not observe splanchnic blood flow and survival rate in this study, other studies have already confirmed that the administration of PR using solutions containing pyruvate could significantly improve those indexes (13,14). Compared with lactate-based peritoneal dialysis solution, PR fluid of pyruvate showed significant protective advantages on its protective effect in cells and organs.…”
Section: Clinical Significancecontrasting
confidence: 67%
See 3 more Smart Citations
“…Even though we did not observe splanchnic blood flow and survival rate in this study, other studies have already confirmed that the administration of PR using solutions containing pyruvate could significantly improve those indexes (13,14). Compared with lactate-based peritoneal dialysis solution, PR fluid of pyruvate showed significant protective advantages on its protective effect in cells and organs.…”
Section: Clinical Significancecontrasting
confidence: 67%
“…Zakaria et al attributed the beneficial effects of PR to the hypertonicity and the contained glucose of the peritoneal dialysis fluid used (5,6). Hu et al compared two kinds of dialysate containing pyruvate with commonly used 2.5% Lac-PDS in an experimental design that excluded the impact of the osmotic pressure (14). Their results showed PY had significant advantages for visceral protection, especially for the small intestine.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…[18,19] However, a sudden influx of liquid into the blood vessels will cause the infused blood to be retained in the venous system as the blood is in a state of stasis in the capillaries, which will cause a constant increase in the intravascular hydrostatic pressure. [13,[20][21][22] In turn, this results in more intravascular liquid penetrating into the extravascular space through the blood vessel walls, which already show increased permeability due to the ischemic and hypoxic injury.…”
Section: Discussionmentioning
confidence: 99%